2021
DOI: 10.1093/genetics/iyab089
|View full text |Cite
|
Sign up to set email alerts
|

WormPaths: Caenorhabditis elegans metabolic pathway annotation and visualization

Abstract: In our group, we aim to understand metabolism in the nematode Caenorhabditis elegans and its relationships with gene expression, physiology and the response to therapeutic drugs. Visualization of the metabolic pathways that comprise the metabolic network is extremely useful for interpreting a wide variety of experiments. Detailed annotated metabolic pathway maps for C. elegans is mostly limited to pan-organismal maps, many with incomplete or inaccurate pathway and enzyme annotations. Here we present WormPaths,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Overall, 315 and 183 genes are induced and repressed by loss of dhgd-1 , respectively ( Table S2 ). WormFlux (Yilmaz and Walhout, 2016) pathway enrichment analysis using pathways defined by WormPaths (Walker et al, 2021) revealed two main insights. First, the propionate shunt is not fully repressed by vitamin B12 in Δ dhgd-1 mutants ( Figures 4A, B, Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 315 and 183 genes are induced and repressed by loss of dhgd-1 , respectively ( Table S2 ). WormFlux (Yilmaz and Walhout, 2016) pathway enrichment analysis using pathways defined by WormPaths (Walker et al, 2021) revealed two main insights. First, the propionate shunt is not fully repressed by vitamin B12 in Δ dhgd-1 mutants ( Figures 4A, B, Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Correlation in expression between metabolic gene pairs across the compendium was calculated as Pearson Correlation Coefficient. Gene set enrichment analysis (GSEA) was performed on the ranked coexpression list using the PreRank module of GSEA (Subramanian et al, 2005) with pathway-to-gene annotations from WormPaths (Walker et al, 2021) and the significance cutoff set at a FDR of less than or equal to 0.05.…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes include dhs-19 , which encodes a short-chain d e h ydrogena s e of unknown function that localizes to lipid droplets 30 and is predicted to function in retinol metabolism 31 . The other two genes, elo-3 and elo-6, both encode elongases predicted to be involved in long chain FA biosynthesis 32, 33 . We generated a dhs-19 deletion mutant by CRISPR/Cas9 genome editing and confirmed that this strain is indeed more sensitive to tamoxifen ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we included annotation lists specific for the commonly used RNAi libraries and found these could reveal enriched pathways in data from an RNAi screen. WormCat has been rapidly adopted by the C. elegans community (Albarqi and Ryder 2021 ; Lee et al 2021 ; Naim et al 2021 ; Tecle et al 2021 ; Zhang et al 2021 ) and adapted into a metabolism-focused tool ( Walker et al 2021 ) as well as an integrated gene expression analysis program ( Cheng et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%